Do green investments impact corporate green innovation?empirical evidence from Chinese-listed companies - Zhang, Yiru; Shou, Songtao; Li, Youhuan (Frontiers in Environmental Science, 2024)
The rapid expansion of the global economy has exacerbated environmental concerns, thereby prompting a shift in resource allocation from polluting industries to green sectors. This transition is pivotal for sustainable development, with capital playing a central role in mobilizing resources to foster green innovation. This study examines data from Chinese-listed companies between 2012 and 2022 to evaluate the impact of green investment on corporate green innovation. The analysis incorporates a comprehensive review of financial records and innovation metrics to establish a correlation between investment and innovation outcomes. The findings reveal a positive correlation between increased green investment and enhanced green innovation, with a more pronounced effect observed in private enterprises and industries characterized by high competition. Green investment primarily stimulates innovation by alleviating financial constraints. These results emphasize the crucial role of green investment in promoting sustainable corporate practices. Furthermore, they provide valuable insights for policymakers in formulating effective green investment strategies, which are essential for China’s transition toward a green economy.